2012
DOI: 10.1038/bjc.2012.376
|View full text |Cite
|
Sign up to set email alerts
|

Does tumour biology determine surgical success in the treatment of epithelial ovarian cancer? A systematic literature review

Abstract: Background:Ovarian cancer is the most lethal gynaecological cancer. Progression-free and overall survival is significantly related to surgical success and residual disease volume. It is unclear whether this survival advantage is due to an intrinsic biological element of the tumour cells which enables successful surgery and improved prognosis, or alternatively the number of tumour sustaining cells remaining irrespective of differences in biology.Methods:A systematic review of the literature was performed identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 61 publications
1
66
1
1
Order By: Relevance
“…предложи-ли панель из 32 генов, которая может прогнозировать успех первичной циторедукции с точностью 72,7 % [37]. Несмотря на научный интерес, экономическая эффек-тивность и проблемы имплементации таких моделей представляют еще бóльшую сложность, а полученные предварительные оптимистичные результаты могут быть подвержены влиянию целого ряда факторов, в первую очередь -особенностей хирургических подходов [38].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…предложи-ли панель из 32 генов, которая может прогнозировать успех первичной циторедукции с точностью 72,7 % [37]. Несмотря на научный интерес, экономическая эффек-тивность и проблемы имплементации таких моделей представляют еще бóльшую сложность, а полученные предварительные оптимистичные результаты могут быть подвержены влиянию целого ряда факторов, в первую очередь -особенностей хирургических подходов [38].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…Recent studies have also investigated the expression of AEG-1/MTDH/LYRIC in ovarian cancer, the most lethal gynecological cancer (Borley, Wilhelm-Benartzi, Brown, & Ghaem-Maghami, 2012; Li et al, 2012; Li, Liu, et al, 2011; Meng, Luo, Ma, Hu, & Lou, 2011). Immunohistochemical staining of AEG-1/MTDH/LYRIC in 81 ovarian cancer patient tissues revealed that high expression of AEG-1/MTDH/LYRIC was detected in 66.7% of ovarian cancer patients in association with clinicopathologic features of the cancer and poor overall survival of the patients when compared with patients with lower expression of AEG-1/MTDH/LYRIC (Meng et al, 2011).…”
Section: Expression Profilementioning
confidence: 99%
“…Briefly, the cells were plated at a density of 6x10 5 cells/well in 6-well plates and allowed to grow overnight at 37˚C. In total, 2 µg of each plasmid DNA and 5 µl Lipofectamine 2000 were diluted separately in Opti-MEM (Gibco; Thermo Fisher Scientific, Inc.) to a total volume of 250 µl.…”
Section: Transient Transfectionmentioning
confidence: 99%
“…Furthermore, recurrence or metastasis occurs in >75% of patients within the first 2 years following initial treatment (3,4). In the majority of patients, initial responses can be achieved with debulking surgery and treatment with taxanes in combination with platinum-based chemotherapy; however, >75% of those responders eventually relapse, resulting in chemoresistant and fatal disease (5,6).…”
Section: Introductionmentioning
confidence: 99%